Xenobates indicus sp. nov. (Hemiptera: Gerromorpha: Haloveliidae) from India, the first species of the genus described from the Indian subcontinent - Jehamalar, E. Eyarin; Dash, Swetapadma; Samuel, Amos Shem (Zootaxa, 2024)
Xenobates indicus sp. nov. is described from Tamil Nadu and West Bengal, India. It constitutes the first species of the genus from the Indian subcontinent. The new species can be identified by its large size when compared to its closely related species and the presence of setal fringe on the posterior margin of mediotergite VIII of female. Key to the species of Xenobates from South and Southeast Asia and the list of world species are provided (Table 1).